2012
DOI: 10.1097/sla.0b013e3182378442
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Versus Standard Multiport Laparoscopic Colectomy

Abstract: SILC is feasible when performed on select patients by surgeons with extensive laparoscopic experience. Outcomes were similar to MLC, except for a reduction in peak pain score on the first postoperative day. Prospective randomized trials should be performed before incorporation of this technology into routine surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
6
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 16 publications
7
140
6
2
Order By: Relevance
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 39%
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 39%
“…Some reports have successfully mentioned its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time. [13][14][15][16][17] To our knowledge, this is the first reported case of SILSþ1 TPE for advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…К насто-ящему времени в мире накоплен существенный опыт та-ких вмешательств [10][11][12][13][14][15][16][17][18][19][20][21]. Пожалуй, наиболее репрезен-тативную выборку (521 SILS и 634 стандартных лапаро-скопических вмешательств при раке ободочной и прямой кишки) представили авторы из Китая, обобщив данные одного проспективного рандомизированного [22] и 13 не-рандомизированных исследований [23]. В подавляющем большинстве работ представляемый опыт не превышает 40 операций, выполненных с помощью технологии еди-ного доступа.…”
Section: результаты и обсуждениеunclassified